Thermal stability evaluation of palm oil - Wan Nik, W. B.; Ani, F. N.; Masjuki, H. H. (Elsevier, 2005)
The thermal stability of palm oil as energy transport media in a hydraulic system was studied. The oils were aged by circulating the oil in an open loop hydraulic system at an isothermal condition of 55C for 600h. The thermal behavior and kinetic parameters of fresh and degraded palm oil, with and without oxidation inhibitor, were studied using the dynamic heating rate mode of a thermogravimetric analyser (TGA). Viscometric properties, total acid number and iodine value analyses were used to complement the TGA data. The thermodynamic parameter of activation energy of the samples was determined by direct Arrhenius plot and integral methods. The results may have important applications in the development of palm oil based hydraulic fluid. The results were compared with commercial vegetable based hydraulic fluid. The use of F10 and L135 additives was found to suppress significantly the increase of acid level and viscosity of the fluid.